2008
DOI: 10.1002/gps.2129
|View full text |Cite
|
Sign up to set email alerts
|

Subjective health‐related quality of life of Chinese older persons with depression in Shanghai and Hong Kong: relationship to clinical factors, level of functioning and social support

Abstract: The high rate of depression in Hong Kong and Shanghai deserves attention. Older people with depression have both psychological and physical health care needs. This study provides insights for healthcare professionals to plan innovative and co-ordinated services that meet the various health care needs of older people with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 34 publications
5
28
0
5
Order By: Relevance
“…We also found that older participants had poorer QOL in the physical health and environment domains than younger people. This result might have been due to older individuals having comorbid medical conditions and less social support in Chinese societies, as reported (Lin et al 2008, Chan et al 2009). Economic issues may have been a critical factor for our participants, but became non-significant in the generalised regression analyses.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We also found that older participants had poorer QOL in the physical health and environment domains than younger people. This result might have been due to older individuals having comorbid medical conditions and less social support in Chinese societies, as reported (Lin et al 2008, Chan et al 2009). Economic issues may have been a critical factor for our participants, but became non-significant in the generalised regression analyses.…”
Section: Discussionmentioning
confidence: 89%
“…, Chan et al . ). Economic issues may have been a critical factor for our participants, but became non‐significant in the generalised regression analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have examined, among other things, supporting older home care clients' resources from the perspective of older people's satisfaction with the care-managed support (Chesterman et al, 2001;Miller, 2011), home support services for older people with dementia (Rothera et al, 2008), and perspective of social support (Chan et al, 2009;Coleman et al, 2011). Home care professionals can support clients' resources to improve their quality of life, provided that the care is client centered and respects clients' autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while the majority of studies demonstrate that the frequency of panic attacks or number of depression symptoms is predictive of disability (Katerndahl & Realini, 1997; Rubin et al . 2000; Chan et al . 2009), others have found that the frequency of panic attacks is not correlated with functioning (Michelson et al .…”
mentioning
confidence: 99%